Analysis of the Implementation of Health Logistics Management in Supporting Service Effectiveness at Clinics - Afrida Dina Pratiwi (Jurnal Kolaboratif Sains, 2026)
Health logistics management is the operational core of healthcare facilities, including independent clinics. The availability of medicines and medical devices in the right type, right quantity, and right time highly determines the quality and effectiveness of medical services. This study aims to analyze in depth the implementation of health logistics management in a primary clinic based on nine operational logistics cycles: planning, procurement, receipt/storage, distribution/maintenance, inventory, elimination, control, recording/reporting, and monitoring and evaluation. The research method used is descriptive qualitative with a case study approach through in-depth interviews with the single person in charge of clinic logistics. The results show that the planning function has run quite well based on historical consumption data of 3-6 months. The implementation of the FEFO/FIFO method is consistently carried out to maintain the quality of medicines. However, several significant structural barriers were found, including a manual-traditional recording system using register books, limited storage space (physical warehouse), limited procurement budget, and a double workload of the informant which triggered administrative delays during busy patient visits. This study recommends the urgency of logistics digitalization through the Electronic Logistics Information System (eLogistics) and optimization of warehouse layout to improve long-term service effectiveness.